2013
DOI: 10.1002/clc.22130
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Paclitaxel‐Coated Balloon Angioplasty in Patients With Drug‐Eluting Stent Restenosis

Abstract: Background:The economic impact of drug-eluting stent (DES) in-stent restenosis (ISR) is substantial, highlighting the need for cost-effective treatment strategies. Hypothesis: Compared to plain old balloon angioplasty (POBA) or repeat DES implantation, drug-coated balloon (DCB) angioplasty is a cost-effective therapy for DES-ISR. Methods: A Markov state-transition model was used to compare DCB angioplasty with POBA and repeat DES implantation. Model input parameters were obtained from the literature, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A large registry demonstrated that TLR after PCB was 9.6% at 9 months in 464 patients with 482 DES restenoses [26]. Given its higher cost [27], however, patient selection is important. In select patients using OCT imaging (focal lesion with heterogeneous pattern by OCT), simple balloon dilatation could be a possible treatment strategy.…”
Section: Other Treatment Optionsmentioning
confidence: 99%
“…A large registry demonstrated that TLR after PCB was 9.6% at 9 months in 464 patients with 482 DES restenoses [26]. Given its higher cost [27], however, patient selection is important. In select patients using OCT imaging (focal lesion with heterogeneous pattern by OCT), simple balloon dilatation could be a possible treatment strategy.…”
Section: Other Treatment Optionsmentioning
confidence: 99%
“…Considering the cost, DCB also met reasonable expectations. Currently, Dorenkamp [27] found that during the six-month follow-up period, the total cost of the DCB treatment strategy was lower than the total cost of the DES treatment (4,028 euros versus 4,101 euros). At the same time, compared with DES, DCB can effectively extend the life of patients (0.497 vs. 0.494).…”
Section: Discussmentioning
confidence: 99%
“…Findings from ongoing studies including STACCATO (Stent sTrut Apposition and Coverage in Coronary ArTeries: an Optical Coherence Tomography (OCT) Study) (BioMatrix [Biosensors Interventional Technologies Pte Ltd, Singapore] vs Xience V [Abbott Vascular, Abbott Laboratories, Abbott Park, Illinois, USA]) and ISAR‐TEST 6 (Intracoronary Stenting and Angiographic Results: Test Efficacy of Biodegradable and Permanent Limus‐Eluting Stents‐6) (Nobori [Terumo Corporation, Tokyo, Japan] vs Xience V) are of substantial value and their publication is eagerly anticipated. PCI represents a huge market in interventional cardiology, and the economic impact of using newer devices should be acknowledged . Subsequent efforts in investigating the cost‐effectiveness of biodegradable polymer DES are also warranted.…”
Section: Discussionmentioning
confidence: 99%